Lamination of chitin-cellulose nanocomposite and thermoplastic starch - Manuzon, Maria Janine D.; Diaz, Leslie Joy S. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Biodegradable materials reduce the debilitating effects of accumulating nonbiodegradable materials to the environment and can become a concrete solution to the probable shortage of raw materials for synthetic polymers. The significance of this study lies in determining satisfactory parameters for laminating a moisture barrier film with another bioplastic to create a composite biodegradable packaging material. This allows for local and naturally abundant components to undergo considerable value addition as an ecofriendly product. Chitin-cellulose films (CC) and nanocomposite (NC) films were successfully laminated to thermoplastic starch (TPS) using adhesive, controlled heated compression, and a combination of both. OSC profiles of the blend, nanocomposite, and TPS samples reveal melting temperatures at 84.82, 79.58, and 96.62 °C, which served as basis for lamination temperature. Qualitative evaluation via tape test (ASTM D3359) was found to be inappropriate for the resulting curved laminates. Pressure, temperature, and use of adhesives were varied. Samples processed at low temperature and pressure were easily delaminated upon removal from the mold, while processing at higher pressure and temperature lead to curvatures and delaminated regions. Use of adhesive without heating brought about better surface finish and more even geometry. Lamination underwent parametric investigation at 2^3 factorial design of experiment in order to produce a laminate with the most acceptable interfacial adhesion measured by direct tensile testing (ASTM D5179). The highest adhesion strength of 0.502±0.036 MPa that resulted for the performed laminations exhibited combination of failure at the interface and substrate for most CC/TPS laminates. This was applied for NCITPS lamination that resulted to a strength of 0.144±0.005 MPa. Three-factor ANOVA by regression showed use of adhesives and temperature to be significant factors, with pvalues lower than ∝ = 0.05. Finally, laminate analysis was done for the samples according to treatment stage by determining tensile properties of the materials (ASTM D882 or ASTM D638). Stress-strain analysis of laminates allowed for determination of modulus of elasticity values of 1.059 ± 0.162 MPa for CC/TPS, and 0.939 ± 0.143 MPa for NC/TPS which improved from 0.342 ± 0.022 MPa for TPS. Poisson's ratios of 0.1891 , 0.3275, and 0.1127, were acquired for CC, NC, and TPS laminas. Experimental values were higher than the theoretical values computed via laminate analysis, with 1.1652and 0.9256 MPa for CC/TPS and NC/TPS. The respective difference in values of 9.1 and 1.4% might have been due to the low R-squared values acquired for slopes in the Poisson's ratio determination. Toughness also increased from 0.122 ± 0.041 MJ/m3 for TPS, to 0.244 ± 0.005 MJ/m3 for CC/TPS, but decreased to 0.091 ± 0.045 MJ/m3 for NC/TPS. Morphological characterization via SEM analysis was done on delaminated and fractured surfaces, and revealed adequate adhesion between CC or NC and TPS that was retained even after fracture from tensile
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Thermop; Biodegradable p; Plastics in pa